Positive effect of home hemodialysis in a pregnant woman with chronic kidney failure during the COVID-19 pandemic: A case report - Andrew Shehata, Dr; Hammad Choudhry, Dr; Darell Hawley; Roma Padalkar (Elsevier, 2021)
This report discusses the case of a 25-year-old pregnant woman from an underserved community, with two previous failed kidney transplants and a previous miscarriage. The patient required a progressive increase to 30 h a week of in-hospital hemodialysis during the COVID-19 pandemic lockdown. She delivered her baby while transitioning to home hemodialysis. Women with end-stage kidney disease who require hemodialysis and wish to become pregnant or who are pregnant have options to allow for a safe and healthy delivery. This can be achieved with vigorous hemodialysis, even at home.